2009
DOI: 10.1017/s0022112008004758
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of internal waves on the sea surface

Abstract: We theoretically analyse the impact of subsurface currents induced by internal waves on nonlinear Stokes surface waves. We present analytical and numerical solutions of the modulation equations under conditions that are close to group velocity resonance. Our results show that smoothing of the downcurrent surface waves is accompanied by a relatively high-frequency modulation, while the profile of the opposing current is reproduced by the surface wave's envelope. We confirm the possibility of generating an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…To satisfy the Laplace equation to second order, Yuen and Lake (1982), Voliak (1998), andHwung et al (2009) suggested an additional phase-shifted term with a linear and quadratic z correction in the representation of the potential function ϕ:…”
Section: Modulation Equations For One-dimensional Interactionmentioning
confidence: 99%
“…To satisfy the Laplace equation to second order, Yuen and Lake (1982), Voliak (1998), andHwung et al (2009) suggested an additional phase-shifted term with a linear and quadratic z correction in the representation of the potential function ϕ:…”
Section: Modulation Equations For One-dimensional Interactionmentioning
confidence: 99%
“…As discussed in the introduction, several previous works used asymptotic analysis to obtain effective reduced models for addressing the surface signature of an IW (Kawahara et al 1975;Hashizume 1980;Funakoshi & Oikawa 1983;Donato et al 1999;Parau & Dias 2001;Bakhanov & Ostrovsky 2002;Barros & Gavrilyuk 2007;Hwung et al 2009;Craig et al 2012). These reduced models mostly focus on either the dynamics of short-mode waves around the resonant k res at sufficiently long times or the linear modulations and the traveling wave solutions for short-mode surface waves.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(ii) Resonant excitations: The rough region travels along with the internal wave; that is, the SW group velocity is close to the internal-wave phase velocity (Osborne & Burch 1980;Kropfli et al 1999;Hwung et al 2009;Craig et al 2012). To understand the above two surface phenomena, we numerically study the surfacewave and interfacial-wave (IW) manifestation in a two-layer, density-stratified system using a weakly nonlinear Boussinesq-type model.…”
Section: Introductionmentioning
confidence: 99%
“…Internal waves could impact the sea surface by altering the approximately two-dimensional velocity field on the surface plane, for example, see Alpers (1985). The convergent/divergent patterns on the surface driven by underlying IWs may manifest themselves through multiple surface modulation mechanisms (Klemas 2012), such as (1) hydrodynamic modulation through IW strains acting on surface wind-generated capillary-gravity waves (Alpers 1985;Hwung, Yang & Shugan 2009), (2) surface film modulation by forming 'slicks' of oceanic surfactants consisting of organic-rich materials (Ewing 1950a;Ermakov, Salashin & Panchenko 1992) under low-wind conditions, and (3) thermal modulation through thickness changes of the 'cool-skin' temperature sublayer (Osborne 1964(Osborne , 1965Zappa & Jessup 2005). Key to these processes is the horizontal divergence…”
Section: Internal Waves Emitted By Localized Stratified Turbulencementioning
confidence: 99%